Romantic Primitivism and Literary Neocolonialism in Camara Laye’s Novel L’Enfant Noir - Panuntun, Ari Bagus; Osmani, Lysa (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2023)
The article examines the depiction of romantic primitivism in Camara Laye’s novel L’Enfant noir (The Dark Child) and the phenomenon of literary neocolonialism behind its publication. L’Enfant noir is a novel published when Guinea was still under French colonization in the 1950s. It tells the story of a happy black child growing up in the middle of a beautiful Guinean countryside, that was completely untouched by the atrocities of colonialism. Upon its publication by Plon, a French publishing house, the novel received different responses from African and European readers. In Africa, it was perceived as turning a blind eye to the cruelty of colonialism. However, in Europe, it was showered with praise and it even received a prestigious literary award. To examine this phenomenon, this article analyzes the novel both intrinsically and extrinsically. Intrinsically, it uses the theory of romantic primitivism to analyze how the novel romanticizes the lives of African indigenous people constrained by colonialism. Extrinsically, it discusses the phenomenon of literary neocolonialism behind the publication of L’Enfant noir. The discussion about literary neocolonialism is divided into two parts. Firstly, it addresses the historical analysis of Plon’s publishing house, its relations with the French power, and the political interests underpinning the novel’s publication. Secondly, it highlights the strategy the publisher uses to accentuate exoticism in the novel’s peritext to market the book in Europe. The novelty of this article lies in its discovery of the elements of romantic primitivism found in the novel while it also proves that literary neocolonialism towards L’Enfant noir persists to this day.